Anti‐Corrosion Elastic Constraints: Redirected Zn Electrodeposition by an Anti‐Corrosion Elastic Constraint for Highly Reversible Zn Anodes (Adv. Funct. Mater. 2/2021). (11th January 2021) - Zhao, Ruirui; Yang, Ying; Liu, Ganxiong; Zhu, Renjie; Huang, Jingbo; Chen, Zhiyuan; Gao, Zhonghui; Chen, Xiao; Qie, Long
Abstract : Aqueous Zinc‐ion batteries are promising systems for large‐scale energy storage applications. In article number 2001867, Long Qie and co‐workers propose an anti‐corrosion elastic constraint (AEC) to reduce parasitic reactions and regulate the electrodeposition of the Zn anodes in aqueous electrolytes. With the help of AEC, Zn anodes with improved cycled stability and enhanced efficiency are achieved.